Detection of biofilm formation by pathogens causing ventilator associated pneumonia at intensive care units in a tertiary care hospital. - Baidya, Sujata (2020)
ABSTRACT: Introduction: Emerging threat of drug resistance among pathogens causing ventilator-associated pneumonia has resulted in increased hospital mortality, length of stay financial burden. Biofilm formation in the endotracheal tube of ventilated patients facilitates the sequestration of invading organisms from the immune system of the host resulting in chronic and recurrent infection that are highly resistant to common antibiotics. This study was intended to determine the biofilm produced by pathogens causing VAP and their relation with the drug resistance. Methods: Broncho-alveolar lavage and deep tracheal aspirate (n=70) were obtained from the patients mechanically ventilated for more than 48 hours in the ICU of TUTH, Kathmandu and processed according to protocol of ASM. Antibiotic susceptibility testing was done following CLSI. Biofilm formation was determined using microtitre plate method described by Christensen and modified by Stepanovoic et al. Data was analyzed using SPSS and tables and charts were prepared using Microsoft Excel. Result: Amidst total samples, 78.6% yielded significant growth with 52.7% monomicrobial and 45.5% polymicrobial infection. 71 isolates were obtained with bulk of the organism comprising of gram-negative isolates accounting for 90.1%. Pseudomonas aeruginosa (31.0%) was the predominant isolate. 56.3% were biofilm producers and 42.3% of total isolates were MDR biofilm producers. High percentage of the biofilm producer was shared by P. aeruginosa. There was no statistically significant association between biofilm production and multidrug resistance however, piperacillin/tazobactam resistance was statistically significant with biofilm production in P. aeruginosa. Conclusion: Gram-negative non-fermenters account for the bulk of the cause of infection in nosocomial settings. The rampant spread of drug resistance among biofilm producers is alarming. Multidrug resistance, ESBL production and MBL production was preponderant in the biofilm producers. Nevertheless, there is necessity of novel interventions to control biofilm-associated infections atributable to their grave outcomes. Keywords: Biofilm, Ventilator-associated Pneumonia, drug resistance, MDR